EXPLORING THE LIFE COURSE EXPERIENCES OF AN ETHNIC MINORITY GROUP AND ITS IMPACT ON THEIR RETIREMENT PLANS: A QUALITATIVE STUDY OF AGING SALVADORIAN IMMIGRANTS IN A COMMUNITY OF SOUTH WESTERN ONTARIO, CANADA - Lemus, Amanda E. (My University, 2013)
In the Canadian context, little is known of the ways in which immigrants’ life course (s) are “mastering of transitions and coordinating life” across geographical space and in differing historical, political, economic and social contexts in their home countries and in their new country unfold (Matthias 2011, p2-3). In order to address this gap in the literature, this qualitative study is focused on the narratives of ten Salvadorian immigrants to examine the different factors that have affected their retirement planning decisions in their new country, Canada. The research study was guided by the Life Course theoretical perspective and considered the role that education, work, and family played in their planning for retirement. Ten Canadian Salvadorian men and women were interviewed using a semi-structured questionnaire. These participants were in the age ranges of mid to later life and included individuals who were not yet retired and individuals who were already retired. As well, this study captured the intersection between structural forces and life courses at the micro level in the pre-migration and post migration experiences of these individuals. Findings show that the effects of historical changes and socioeconomic status were carried over to Canada and that these constrained or produced opportunities that had varying implications for retirement planning. As a consequence, the majority of individuals prioritize their needs to here and now rather than to here and tomorrow.
Keywords: planning for later life; ethnic minority; Salvadorian Canadians; aging; ageing; life course; Other Social and Behavioral Sciences; Social and Behavioral Sciences; Other Social and Behavioral Sciences